Equity Misvaluation and Default Options - EISDORFER, ASSAF; GOYAL, AMIT; ZHDANOV, ALEXEI (Journal of Finance, 2019)
ABSTRACT We study whether default options are mispriced in equity values by employing a structural equity valuation model that explicitly takes into account the value of the option to default (or abandon the firm) and uses firm‐specific inputs. We implement our model on the entire cross section of stocks and identify both over‐ and underpriced equities. An investment strategy that buys undervalued stocks and shorts overvalued stocks generates an annual four‐factor alpha of about 11% for U.S. stocks. The model's performance is stronger for stocks with a higher value of the default option, such as distressed or highly volatile stocks.